GROWTH AND COLOUR PIGMENTATION OF CLARIAS GARIEPINUS FED WITH FEED FORMULATED WITH CARROT (DAUCUS CAROTA) AND TURMERIC (CURCUMA LONGA) - ONUOHA, P. C; UMEH, W. (Nigerian Journal of Fisheries, 2021)
The experiment assessed the growth and pigmentation of Clarias gariepinus feed with two carotenoid-containing feed ingredients; carrot and turmeric. The work was carried out in a completely randomized design with three treatments which were in triplicates. Treatment 1, 2, and 3 were feed formulated with 10% turmeric inclusion, 10% carrot inclusion, and the control with no carrot or turmeric included, respectively. Fish feed wereformulated, and the fish were fed 5% of their body weight, twice daily. Sampling was done biweekly and feed weights were adjusted accordingly. Water quality parameters were monitored and recorded, growth parameterswere calculated from the fish weight. The initial and final carotenoid content of the fish were measured as well as organoleptic test. The result of the physicochemical parameters showed that there were no significant differences (p>0.05) amongst the treatments. The growth result also showed no significant differences (p>0.05) amongst the treatments. The carotenoid content of the fish showed significant differences (p<0.05) amongst the treatments for the final carotenoid content and the change in the level of carotenoid content. Treatment 2 provedto have higher carotenoid content than the others. Feed with carrot inclusion did better amongst the other treatments and show greater pigmentation.